2019 update of the WSES guidelines for management of Clostridioides (Clostridium) difficile infection in surgical patients - Sartelli, Massimo; Di Bella, Stefano; McFarland, Lynne V; Khanna, Sahil; Furuya-Kanamori, Luis; Abuzeid, Nadir; Abu-Zidan, Fikri M; Ansaloni, Luca; Augustin, Goran; Bala, Miklosh; Ben-Ishay, Offir; Biffl, Walter L; et al. (World journal of emergency surgery, 2019)
In the last three decades, Clostridium difficile infection (CDI) has increased in incidence and severity in many countries worldwide. The increase in CDI incidence has been particularly apparent among surgical patients. Therefore, prevention of CDI and optimization of management in the surgical patient are paramount. An international multidisciplinary panel of experts from the World Society of Emergency Surgery (WSES) updated its guidelines for management of CDI in surgical patients according to the most recent available literature. The update includes recent changes introduced in the management of this infection.
Keywords: směrnice jako téma; Enterocolitis, Pseudomembranous; kontrola infekce; pseudomembranózní enterokolitida; lidé; Anti-Bacterial Agents; klostridiové infekce; pooperační komplikace; Risk Factors; Incidence; Clostridium Infections; fekální transplantace; Fecal Microbiota Transplantation; Guidelines as Topic; Postoperative Complications; incidence; rizikové faktory; Clostridioides difficile; Infection Control; antibakteriální látky; Antimicrobial Stewardship; antibiotická politika; Humans